Valvular heart disease in patients with Parkinson's disease treated with pergolide, levodopa or both - ÖZBEN SADIÇ, BESTE (ELSEVIER SCI LTD, 2009)
Cardiac valvulopathy has been reported ill patients with Parkinson's disease treated with pergolide. The aim of this Study was to clarify the frequency and severity of valvular heart disease (VHD) in patients treated with pergolide, levodopa or both. We evaluated VHD by transthoracic echocardiography in 25 patients who were taking pergolide, 29 patients taking levodopa and 20 patients taking both levodopa and pergolide. All groups were compared with two separate age-matched control groups. There was no increase ill the frequency of any type of echocardiographically-significant Valvulopathy in the periodic groups. significant aortic regurgitation was found in 8% of the patients in the pergolide group and ill 37.9% of the patients in the levodopa group. There was no correlation between VHD and pergolide dose. cumulative dose or duration of therapy. The mean pergolide dose was 2.6 +/- 1.4 mg/day in the pergolide monotherapy group. We did not find any unequivocal evidence that pergolide causes significant valvular regurgitation. However. the mean pergolide dosage ill our study was lower than ill previous studies. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Levodopa; Parkinson's disease; Pergolide; Valvulopathy; DERIVATIVE DOPAMINE AGONISTS; DOPPLER-ECHOCARDIOGRAPHY; VALVE DISEASE; TASK-FORCE; REGURGITATION; RECOMMENDATIONS; FENFLURAMINE; COMMITTEE